2016
DOI: 10.1063/1.4967779
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic estimation the compressibility of ferropericlase under high pressure

Abstract: The elastic properties of (Mg1-xFex)O ferropericlase are essential to analyze seismic data and to constrain its chemical composition in the lower mantle. In this study, we suggest a simple thermodynamic model that enables the estimation of the bulk moduli of (Mg1−xFex)O ferropericlase as a function of component x in terms of the elastic data of the end members. Our calculated bulk moduli compare favorably with reported experimental data when uncertainties are considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Along these lines, they followed the method proposed by Varotsos and Alexopoulos [12] to explain how the compressibility κ(= 1/B) of a solid solution A 1−x B x is interrelated with the compressibilities of two end members A and B upon using the cBΩ model. Zhang and Xu [52] stated that they found an excellent consistency between the calculated B values and the experimental ones in ferropericlase. Hence, they concluded that this method based on the cBΩ model exhibits credibility of describing compresibility in terms of the bulk moduli of the two end members, i.e., MgO and FeO; thus, it constitutes an interesting method to determine the compressibility of Earth materials with complicated structure using the measured compressibilities of their end members.…”
Section: Applications Of Usefulness In Geophysics and Seismologymentioning
confidence: 74%
See 1 more Smart Citation
“…Along these lines, they followed the method proposed by Varotsos and Alexopoulos [12] to explain how the compressibility κ(= 1/B) of a solid solution A 1−x B x is interrelated with the compressibilities of two end members A and B upon using the cBΩ model. Zhang and Xu [52] stated that they found an excellent consistency between the calculated B values and the experimental ones in ferropericlase. Hence, they concluded that this method based on the cBΩ model exhibits credibility of describing compresibility in terms of the bulk moduli of the two end members, i.e., MgO and FeO; thus, it constitutes an interesting method to determine the compressibility of Earth materials with complicated structure using the measured compressibilities of their end members.…”
Section: Applications Of Usefulness In Geophysics and Seismologymentioning
confidence: 74%
“…We now turn to ferropericlase (Mg,Fe)O, which is widely believed to be a major phase in the lower mantle of the Earth, coexisting with Mg-rich silicate perovskite, (Mg,Fe,Al)SiO 3 . Since the elastic properties of (Mg 1−x Fe x )O ferropericlase are essential to analyze seismic data and to constrain its chemical composition in the lower mantle, Zhang and Xu [52] proceeded to the estimation of the bulk moduli of (Mg 1−x Fe x )O ferropericlase as a function of component x in terms of the elastic data of the end members. Along these lines, they followed the method proposed by Varotsos and Alexopoulos [12] to explain how the compressibility κ(= 1/B) of a solid solution A 1−x B x is interrelated with the compressibilities of two end members A and B upon using the cBΩ model.…”
Section: Applications Of Usefulness In Geophysics and Seismologymentioning
confidence: 99%
“…The calculated activation enthalpy is in agreement with the recently reported experimental value and the corresponding activation volume suggests the interstitial diffusion mechanism. The present study can serve as a paradigm to related work on the defect processes of semiconductors and oxides [49][50][51][52].…”
Section: Discussionmentioning
confidence: 96%
“…There are numerous applications of the SQS and cBΩ model methodologies in the literature [64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83]. This is driven by the introduction of new material systems and the requirement for easy and inexpensive screening in an effort to lead to application as soon as possible.…”
Section: Advanced Materials For Energy Applicationsmentioning
confidence: 99%